2014
DOI: 10.1096/fj.13-244202
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive β 2 ‐agonist treatment reduces glycogen independently of receptor‐mediated acid α‐glucosidase uptake in the limb muscles of mice with Pompe disease

Abstract: Enzyme or gene replacement therapy with acid α-glucosidase (GAA) has achieved only partial efficacy in Pompe disease. We evaluated the effect of adjunctive clenbuterol treatment on cation-independent mannose-6-phosphate receptor (CI-MPR)-mediated uptake and intracellular trafficking of GAA during muscle-specific GAA expression with an adeno-associated virus (AAV) vector in GAA-knockout (KO) mice. Clenbuterol, which increases expression of CI-MPR in muscle, was administered with the AAV vector. This combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…15 We observed the same phenomenon in the current study; however, the greatest clearance of the accumulated glycogen in heart was observed by adding anti-CD4 mAb treatment to suppress anti-GAA formation. A synergistic effect on glycogen clearance was demonstrated after triple therapy in the heart, diaphragm, and quadriceps, which reduced glycogen content to the lowest concentration observed in each of these muscles (Fig.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…15 We observed the same phenomenon in the current study; however, the greatest clearance of the accumulated glycogen in heart was observed by adding anti-CD4 mAb treatment to suppress anti-GAA formation. A synergistic effect on glycogen clearance was demonstrated after triple therapy in the heart, diaphragm, and quadriceps, which reduced glycogen content to the lowest concentration observed in each of these muscles (Fig.…”
Section: Resultssupporting
confidence: 86%
“…11 However, a muscle-specific GAA expression vector, AAV2/8-MHCK7hGAApA, did not clear accumulated glycogen from the heart and skeletal muscles despite a large increase in the observed GAA activity. 15 We observed this phenomenon again in the current study (Fig. 1).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…69 Notably, Albuterol-reduced muscular glycogen even independently from receptor-mediated GAA uptake in the murine model. 70 Another strategy is the use of small molecules known as pharmacological chaperones, which bind to the mutant enzyme and recover its lysosomal activity by correcting the protein folding. 71,72 However, the presence of a misfolded enzyme with recoverable function is essential for an effect of this class of drug.…”
mentioning
confidence: 99%